Spatiotemporal Diversification of Global Junipers: Traces of Niche Conservatism and Trait‐Dependent Diversification - Rodrigo Martínez de León; Alejandra Moreno‐Letelier (Ecology and Evolution, 2025)
ABSTRACT Speciation rates differ globally across phylogenies and regions, and the complexity of the speciation process makes it difficult to fully understand these variations. It has been suggested that in conifers, the speciation process is primarily influenced by abiotic factors, operating in a local adaptive dynamic. In this study, we investigate changes in the climatic envelopes of conifer species of the genus Juniperus and test their explanatory power in predicting the distribution of speciation rates in space controlling for other explanatory factors such as topography and morphology. Location: Northern Hemisphere. Taxon: Juniperus. We used phylogenetic comparative methods and macroecological methods to evaluate speciation rate shifts, trait‐speciation correlations, trait‐geography correlations, and areas of phylogenetic endemism. Climatic niches in the juniper species follow bimodal trends in temperature and precipitation variables. These trends imply a strong event of divergence or possible adaptation that is trackable to a specific moment and geography. Additionally, we found significant explanatory power for some climatic variables and a heterogeneous response by continent, with morphological changes being the most important in North America, whereas climate is more relevant in the Tibetan Plateau. Centers of diversity follow different trends in phylogenetic diversity and endemism, suggesting different causes of diversity. Overall, junipers exhibit a conserved climatic niche, and their speciation process is marked by the particular history of their distribution rather than by general trends in climatic evolution. Morphological evolution is more important than previously considered and both accumulation of lineages and rapid speciation are supported for hotspot regions.